ANALISIS PERBANDINGAN KONTRIBUSI DAN EFEKTIVITAS PAJAK BAHAN BAKAR KENDARAAN BERMOTOR DI PROVINSI GORONTALO DAN PROVINSI SULAWESI UTARA - Dalonto, Miswati; Sondakh, Jullie J.; Tangkuman, Steven J. (Universitas Sam Ratulangi, 2019)
The contribution and the effectiveness of motorcycle fuel taxas is one of the tools that can measure how far the contribution of motorcycle fuel taxes towards original local government revenue and also how far the achievements level of tax collaction by local government in regards of motorcycle fuel taxes because of tax incomes is very crucial to build a district. This study aims to (1) Determine how big the contribution motorcycle fuel taxes toword Original government revenue in Gorontalo Province and North Sulawesi Province (2) To Determine how big the effectiveness motorcycle fuel taxes in Gorontalo Province and North Sulawesi Province (3) How the comparison of contribution and the effectiveness of motorcycle fuel taxes in Gorontalo Province and North Sulawesi Province. This study is using qualitative descriptive method. The result of this study is showing that the motorcycle fuel taxes in Gorontalo Province is stil lack of giving contribution because of the result shows that the average of percentage is 19,29%, and on the other side, North Sulawesi Province also shows a lack of giving contribution which is 19,75% in percentage, and effectiveness motorcycle fuel taxes in Gorontalo Province and North Sulawesi Province is included as very effective criteria by showing a result of criteria level is more than 100%.